Resin composition and product thereof

By using a copolymer of phenylvinyl silane and alkenyl compound and a resin composition of styrene-capped phenolic resin, the problem of high volatility of resin materials at high temperatures is solved, the performance of copper clad material is improved, and the comprehensive performance requirements of high-frequency and high-speed substrates are met.

CN119912781AActive Publication Date: 2025-05-02ELITE ELECTRONIC MATERIAL(ZHONGSHAN)CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311422049.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02
Estimated Expiration
2043-10-30

AI Technical Summary

Technical Problem

Existing resin materials are prone to evaporation during high-temperature processing, resulting in waste of raw materials and changes in the properties of copper clad materials, which cannot meet the comprehensive performance requirements of high-frequency and high-speed substrates.

Method used

Using a resin composition, including a copolymer of phenylvinylsilane and an alkenyl compound and a styrene-capped phenolic resin, the volatile property is reduced and the material properties are improved by adjusting the raw material ratio and reaction conditions of the copolymer.

Benefits of technology

It effectively reduces the volatility of the resin material, improves the glass conversion temperature, copper foil tension, dielectric constant, dielectric loss, thermal expansion rate and PCT heat resistance of copper clad material, and meets the comprehensive performance requirements of high-frequency and high-speed substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912781A_ABST
    Figure CN119912781A_ABST
Patent Text Reader

Abstract

The invention discloses a resin composition which comprises the following components in parts by weight: 100 parts of copolymer of phenyl vinyl silane and alkenyl compound, and 20-100 parts of styrene-terminated phenolic resin, the copolymer of the phenyl vinyl silane and the alkenyl compound comprises the following raw materials in parts by weight: 80-98 parts of the phenyl vinyl silane and 2-20 parts of the alkenyl compound, based on 100 parts of the total weight of the phenyl vinyl silane and the alkenyl compound, the weight of the phenyl vinyl silane is 80-98 parts, and the weight of the alkenyl compound is 2-20 parts. The resin composition can be prepared into products such as prepregs, resin films, laminated boards, printed circuit boards or cured insulators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of resin compositions, and in particular to a resin composition and a product thereof which can be used for preparing a prepreg, a resin film, a laminate, a printed circuit board or a cured insulator. Background Art

[0002] In recent years, as the information processing of electronic products such as mobile communications, servers, and cloud storage continues to develop in the direction of high-frequency signal transmission and high-speed digitalization, low-dielectric resin materials have become the main development direction of high-frequency and high-speed substrates. In the manufacture of copper-clad laminate materials, the raw material phenyl vinyl silane is easily volatilized due to high-temperature heating during the material processing process. Direct use not only causes a waste of expensive raw materials, but also causes changes in the properties of the copper-clad laminate material and fails to meet the performance requirements.

[0003] Therefore, how to optimize and improve the resin material to reduce its volatility and improve the comprehensive performance of the copper clad laminate material, such as glass transition temperature, copper foil tensile force, thermal expansion rate and thermal expansion coefficient, PCT heat resistance, dielectric constant, dielectric loss and other one or more characteristics, is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0004] In view of the problems encountered in the prior art, the present invention provides a resin composition that can be used to prepare a semi-cured sheet, a resin film, a laminate, a printed circuit board or a cured insulator to solve the problems of high volatility of resin products in the prior art and the inability to meet the requirements of one or more of the above-mentioned properties.

[0005] In a first aspect, the present invention provides a resin composition, which comprises, by weight: 100 parts of a copolymer of phenyl vinyl silane and an alkenyl compound, and 20 to 100 parts of a styrene-terminated phenolic resin;

[0006] The copolymer of phenylvinylsilane and alkenyl compound includes structural units formed by phenylvinylsilane and alkenyl compound; the raw materials of the copolymer include phenylvinylsilane and alkenyl compound, and based on the total weight of phenylvinylsilane and alkenyl compound as 100 parts by weight, the phenylvinylsilane is 80 parts by weight to 98 parts by weight, and the alkenyl compound is 2 parts by weight to 20 parts by weight.

[0007] The phenylvinylsilane has a structure represented by formula (1) and / or formula (2), the alkenyl compound has a structure represented by formula (3), and the styrene-terminated phenolic resin has a structure represented by formula (4):

[0008]

[0009]

[0010] wherein Ra, Rb, Rc, and Rd are each independently H or a monovalent organic group, m and n are each independently an integer from 0 to 5, and Re, Rf, Rg, and Rh are each independently H or a monovalent alkyl group having 1 to 4 carbon atoms;

[0011] Furthermore, R is a divalent organic group, and n1 is an integer of 1 to 30.

[0012] In an optional embodiment, R is at least one of a methylene group, a biscyclopentadienyl group, and a substituted or unsubstituted arylene group, and n1 is an integer from 1 to 10.

[0013] In an optional embodiment, the chemical structure of the alkenyl compound is at least one of formula (11), formula (12) or formula (13):

[0014] 2,4-Diphenyl-4-methyl-1-pentene:

[0015] 2,4-Diphenyl-3,4-dimethyl-1-hexene:

[0016] 2,4-Di(p-methoxy)phenyl-4-methyl-1-pentene:

[0017] In a second aspect, the present invention provides a product, which is made of the above-mentioned resin composition, and the product includes but is not limited to a prepreg, a resin film, a laminate, a printed circuit board or a cured insulator.

[0018] In an optional embodiment, the resin composition or its product provided by the present invention can be improved in one or more aspects such as glass transition temperature, copper foil tensile force, dielectric constant, dielectric loss, thermal expansion rate, thermal expansion coefficient or PCT heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 It is an infrared spectrum of the copolymer 3 of the present invention, phenyltrivinylsilane and 2,4-diphenyl-4-methyl-1-pentene; wherein a is 2,4-diphenyl-4-methyl-1-pentene, b is phenyltrivinylsilane, and c is copolymer 3;

[0021] Figure 2 The nuclear magnetic hydrogen spectrum of the copolymer 3 of the present invention, phenyltrivinylsilane and 2,4-diphenyl-4-methyl-1-pentene; wherein a is phenyltrivinylsilane, b is 2,4-diphenyl-4-methyl-1-pentene, and c is copolymer 3;

[0022] Figure 3 It is the gel permeation chromatogram of copolymer 3 of the present invention. DETAILED DESCRIPTION

[0023] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0024] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0025] In order to enable ordinary technicians in the field to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text have the common meanings understood by ordinary technicians in the field for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] In the present invention, the terms "include", "comprising", "having", "containing" or any other similar terms are open-ended transitional phrases, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "P or Q": P is true (or exists) and Q is false (or does not exist), P is false (or does not exist) and Q is true (or exists), and P and Q are both true (or exist). In addition, in the present invention, the interpretation of the terms "include", "comprising", "having", and "containing" should be considered to have specifically disclosed and simultaneously cover closed transitional phrases such as "consisting of..." and transitional phrases such as "consisting essentially of..."

[0027] In the present invention, all features or conditions defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values ​​within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all sub-ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially the sub-ranges defined by all integer values, and should be deemed to have specifically disclosed individual values ​​such as 1, 2, 3, 4, 5, 6, 7, 8, etc. in the range. Similarly, the range description of "between 1 to 8" should be deemed to have specifically disclosed all ranges such as 1 to 8, 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, and include endpoint values. Unless otherwise specified, the above interpretation method applies to all contents of the present invention, regardless of whether the scope is wide or not.

[0028] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that the present invention has specifically disclosed all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range, regardless of whether such ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0029] In the present invention, under the premise of achieving the purpose of the invention, numerical values ​​should be understood to have the accuracy of the significant digits of the numerical value. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.

[0030] In the present invention, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that subgroups or any individual members of all members in the Markush group or option list can also be used to describe the present invention. For example, if X is described as "selected from the group consisting of X1, X2 and X3", it also means that the claim that X is X1 and the claim that X is X1 and / or X2 and / or X3 have been fully described. Furthermore, for those who use Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that any combination of subgroups or individual members of all members in the Markush group or option list can also be used to describe the present invention. Accordingly, for example, if X is described as "selected from the group consisting of X1, X2 and X3", and Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that the claim that X is X1 or X2 or X3 and Y is Y1 or Y2 or Y3 has been fully described. As used herein, "or a combination thereof" means "or any combination thereof".

[0031] If not otherwise specified, "resin" is generally a customary name for a synthetic polymer, but in the present invention, "resin" may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, and is not limited thereto. For example, "maleimide resin" in the present invention may include maleimide monomers (maleimide small molecule compounds), maleimide polymers, combinations of maleimide monomers, combinations of maleimide polymers, and combinations of maleimide monomers and maleimide polymers.

[0032] In the structural formula herein, "*" indicates a bonding site.

[0033] Unless otherwise specified, in the present invention, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, and is not limited thereto. In the present invention, a compound is not limited to a single chemical substance when interpreted, but can also be interpreted as the same type of chemical substance with the same composition or the same properties. In addition, in the present invention, a mixture refers to a combination of two or more compounds, and the mixture may also include copolymers or other additives, etc., and is not limited thereto.

[0034] Unless otherwise specified, in the present invention, polymer refers to the product formed by the polymerization reaction of monomers, which often includes the aggregates of many macromolecules, each of which is composed of many simple structural units repeatedly connected by covalent bonds, and the monomer is the compound that synthesizes the polymer. The polymer may include homopolymers (also known as autopolymers), copolymers, prepolymers, etc., but is not limited thereto.

[0035] Homopolymer refers to a chemical substance formed by polymerization, addition polymerization, and condensation polymerization of a single compound. Copolymer refers to a chemical substance formed by polymerization, addition polymerization, and condensation polymerization of two or more compounds, including random copolymers (structures such as -AABABBBAAABBA-), alternating copolymers (structures such as -ABABABAB-), graft copolymers (structures such as -AA(A-BBBB)AA(A-BBBB)AAA-), and block copolymers (structures such as -AAAAA-BBBBBB-AAAAA-), etc. Unless otherwise specified, the copolymer in the present invention refers to a polymer obtained by copolymerizing monomers of phenylvinylsilane, divinylbenzene, and styrene. The copolymer in the present invention can be a copolymer having phenylvinylsilane, divinylbenzene, and styrene segments at the same time, and there is no special limitation on whether the units of the main chain skeleton and the side chain of the polymer are modified or modified.

[0036] If not otherwise specified, in the present invention, a prepolymer refers to a polymer with a lower molecular weight between the monomer and the final polymer, and the prepolymer contains reactive functional groups that can be further polymerized to obtain a fully cross-linked or hardened product with a higher molecular weight.

[0037] Polymers include, but are not limited to, oligomers. Oligomers, also known as low polymers, are polymers composed of 2-20 repeating units, usually 2-5 repeating units.

[0038] If not specifically indicated, in the present invention, modified products (also referred to as modified products) include products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after homopolymerization of each resin, products after copolymerization of each resin with other resins, etc. For example, but not limited to, modification may be to replace the original hydroxyl group with a vinyl group through a chemical reaction, or to obtain a terminal hydroxyl group by chemically reacting the original terminal vinyl group with p-aminophenol.

[0039] Unless otherwise specified, the alkyl, alkenyl and hydrocarbon groups described in the present invention include their various isomers when interpreted. For example, propyl should be interpreted as including n-propyl and isopropyl.

[0040] Unless otherwise specified, the term "vinyl-containing" in the present invention refers to a compound structure containing an ethylene carbon-carbon double bond (C=C) or a functional group derived therefrom. Therefore, examples of vinyl-containing compounds may include, but are not limited to, compounds containing functional groups such as vinyl, allyl, vinylbenzyl, and methacrylate groups in the structure. Unless otherwise specified, the positions of the aforementioned functional groups are not particularly limited, and may be located at the end of a long chain structure, for example. Therefore, for example, a vinyl-containing polyphenylene ether resin represents a polyphenylene ether resin containing functional groups such as vinyl, allyl, vinylbenzyl, and methacrylate groups, and is not limited thereto.

[0041] If not otherwise specified, the unsaturated bond described in the present invention refers to a reactive unsaturated bond, such as but not limited to an unsaturated double bond that can undergo a cross-linking reaction with other functional groups, such as but not limited to an unsaturated carbon-carbon double bond that can undergo a cross-linking reaction with other functional groups.

[0042] In the present invention, parts by weight represent parts by weight, which can be any weight unit, such as but not limited to kilograms, grams, pounds, etc. For example, 100 parts by weight of the vinyl-containing polyphenylene ether resin can represent 100 kilograms of the vinyl-containing polyphenylene ether resin or 100 pounds of the vinyl-containing polyphenylene ether resin.

[0043] Embodiments of the present invention

[0044] In a first aspect, the present invention provides a resin composition, which comprises, by weight: 100 parts of a copolymer of phenyl vinyl silane and an alkenyl compound, and 20 to 100 parts of a styrene-terminated phenolic resin;

[0045] In an optional embodiment, compared to 100 parts by weight of the copolymer of phenylvinylsilane and alkenyl compound, the resin composition comprises 20 to 100 parts by weight of styrene-terminated phenolic resin. For example, in an optional embodiment, compared to 100 parts by weight of the copolymer, the styrene-terminated phenolic resin is 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight or 95 parts by weight, and is not limited thereto.

[0046] In an optional embodiment, the copolymer of phenylvinylsilane and alkenyl compound includes a structural unit formed by phenylvinylsilane and alkenyl compound. The raw materials of the copolymer include phenylvinylsilane and alkenyl compound, and the total weight of phenylvinylsilane and alkenyl compound is 100 parts by weight, wherein phenylvinylsilane is 80 to 98 parts by weight, and alkenyl compound is 2 to 20 parts by weight. For example, in an optional embodiment, the weight of the phenylvinylsilane is, for example, but not limited to, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight or 98 parts by weight; the weight of the alkenyl compound is, for example, but not limited to, 2 parts by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight or 20 parts by weight. For another example, the weight parts of phenylvinylsilane and the alkenyl compound are 80 parts by weight and 20 parts by weight respectively; for another example, the weight parts of phenylvinylsilane and the alkenyl compound are 85 parts by weight and 15 parts by weight respectively; for another example, the weight parts of phenylvinylsilane and the alkenyl compound are 90 parts by weight and 10 parts by weight respectively; for another example, the weight parts of phenylvinylsilane and the alkenyl compound are 95 parts by weight and 5 parts by weight respectively; for another example, the weight parts of phenylvinylsilane and the alkenyl compound are 98 parts by weight and 2 parts by weight respectively.

[0047] In an optional embodiment, in the copolymer of phenylvinylsilane and an alkenyl compound, the content of the structural unit formed by phenylvinylsilane is 78 mol% to 99 mol%, for example, but not limited to 78 mol%, 79 mol%, 80 mol%, 81 mol%, 82 mol%, 83 mol%, 84 mol%, 85 mol%, 86 mol%, 87 mol%, 88 mol%, 89 mol%, 90 mol%, 91 mol%, 92 mol%, 93 mol%, 94 mol%, 95 mol%, 96 mol%, 97 mol%, 98 mol%, 99 mol%.

[0048] In an optional embodiment, in the copolymer of phenylvinylsilane and alkenyl compound, the content of the structural unit formed by the alkenyl compound is 1 mol% to 20 mol%, for example but not limited to 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, 17 mol%, 18 mol%, 19 mol%, 20 mol%.

[0049] In an optional embodiment, the weight average molecular weight of the copolymer of phenylvinylsilane and alkenyl compound is between 2,000 and 50,000, for example but not limited to 2,000, 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000 or 50,000, for example, the weight average molecular weight of the copolymer is 32,071, and for example, the weight average molecular weight of the copolymer is 3,686.

[0050] In an optional embodiment, the preparation method of the copolymer of phenylvinylsilane and alkenyl compound comprises: reacting 80 to 98 parts by weight of phenylvinylsilane and 2 to 20 parts by weight of alkenyl compound. In an optional embodiment, the reaction is carried out at 80° C. to 150° C. for 2 to 10 hours. In an optional embodiment, the preparation method of the copolymer further comprises the steps of purification (i.e., purification, also known as increasing its purity), filtering or drying.

[0051] In an optional embodiment, the reaction time may be between 2 hours and 10 hours, such as between 3 hours and 9 hours, or between 4 hours and 8 hours, or between 5 hours and 7 hours. In an optional embodiment, the reaction temperature may be between 80°C and 150°C, such as between 90°C and 140°C, or between 100°C and 130°C, or between 110°C and 120°C. In an optional embodiment, the purification is recrystallization using an alcohol solvent.

[0052] In an optional embodiment, the preparation method further comprises adding a curing accelerator, wherein the curing accelerator comprises an initiator, a catalyst or a combination thereof. The amount of the curing accelerator is 0.1% to 1.5% of the sum of the weight of the phenylvinylsilane and the alkenyl compound, for example, between 0.2% and 1.4%, or between 0.3% and 1.3%, or between 0.4% and 1.2%, or between 0.5% and 1.1%, or between 0.6% and 1.0%, or between 0.7% and 0.9%.

[0053] In an optional embodiment, the initiator is at least one of bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, dibenzoyl peroxide, 2,3-dimethyl-2,3-diphenylbutane, diisopropyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, and azobisisobutylonitrile, and is not limited thereto.

[0054] In an alternative embodiment, the catalyst comprises a metal carboxylate.

[0055] In an optional embodiment, the preparation method further comprises using a solvent, wherein the amount of the solvent is 0% to 100% of the sum of the weight of the phenylvinylsilane and the alkenyl compound, for example, between 10% and 90%, or between 20% and 80%, or between 30% and 70%, or between 40% and 60%.

[0056] In an optional embodiment, the solvent is at least one of methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, and propylene glycol methyl ether, and is not limited thereto.

[0057] In an optional embodiment, the phenylvinylsilane is a structure represented by formula (1) and / or formula (2), and the alkenyl compound is a structure represented by formula (3):

[0058]

[0059] Wherein, Ra, Rb, Rc, and Rd are each independently H or a monovalent organic group, m and n are each independently an integer from 0 to 5, and Re, Rf, Rg, and Rh are each independently H or a monovalent alkyl group having 1 to 4 carbon atoms.

[0060] In an optional embodiment, the monovalent organic group includes at least one of an alkyl, an alkoxy, a substituted or unsubstituted aryl or benzyl, a substituted or unsubstituted aryloxy or benzyloxy. For example, the monovalent organic group examples include methyl, ethyl, propyl, butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, phenyl, benzyl, methoxy, ethoxy, propoxy, butoxy, phenoxy, benzyloxy, etc., and are not limited thereto. In an optional embodiment, the monovalent organic group may be a monovalent alkyl or alkoxy group having 1 to 10 carbon atoms. In an optional embodiment, the monovalent organic group may be a monovalent alkyl or alkoxy group having 1 to 4 carbon atoms.

[0061] In an alternative embodiment, the monovalent alkyl group having 1 to 4 carbon atoms may be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl.

[0062] In an optional embodiment, the copolymer of phenylvinylsilane and alkenyl compound comprises structural unit A and structural unit B, wherein the structural unit A is at least one of the structures represented by formula (5), formula (6), formula (7), formula (8), and formula (9), and the number of structures represented by formula (5), formula (6), formula (7), formula (8), and formula (9) in the copolymer is J1, J2, J3, K1, and K2, respectively;

[0063]

[0064] The structural unit B is a structure represented by formula (10), and the number of the structures represented by formula (10) in the copolymer is L1;

[0065]

[0066] Wherein, * represents the bonding position, J1, J2, J3, K1, K2 are each independently 0 or a positive integer, but not 0 at the same time (that is, at least one of J1, J2, J3, K1 and K2 is not 0), and L1 is a positive integer; and 10≤J1+J2+J3+L1≤268, or 8≤K1+K2+L1≤212, or 8≤J1+J2+J3+K1+K2+L1≤268.

[0067] For example, in one embodiment, the J1 and J2 are each independently an integer greater than or equal to 1, and J3, K1, and K2 are each independently an integer greater than or equal to 0. In one embodiment, the J1, J2, and J3 are each independently an integer greater than or equal to 0, and K1 and K2 are each independently an integer greater than or equal to 1. In one embodiment, the J1, J2, K1, and K2 are each independently an integer greater than or equal to 1, and J3 is an integer greater than or equal to 0.

[0068] In an optional embodiment, the copolymer includes structures as shown in formula (5), formula (6), formula (7) and formula (10), and the number thereof is, for example but not limited to, J1+J2+J3+L1=10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260 or 268. In an optional embodiment, the copolymer includes structures as shown in formula (8), formula (9) and formula (10), and the number thereof is, for example but not limited to, K1+K2+L1=8, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210 or 212. In an optional embodiment, the copolymer includes structures as shown in formula (5), formula (6), formula (7), formula (8), formula (9) and formula (10), and the number thereof is, for example but not limited to, J1+J2+J3+K1+K2+L1=8, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260 or 268.

[0069] In an optional embodiment, the chemical structure of the alkenyl compound is at least one of formula (11), formula (12) or formula (13):

[0070] 2,4-Diphenyl-4-methyl-1-pentene:

[0071] 2,4-Diphenyl-3,4-dimethyl-1-hexene:

[0072] 2,4-Di(p-methoxy)phenyl-4-methyl-1-pentene:

[0073] In an optional embodiment, the styrene-terminated phenolic resin used in the present invention is a phenolic resin with a styrene group obtained by reacting the hydroxyl group in the phenolic resin with a compound containing a styrene group, and the styrene group is at the end of the resin molecular structure or on the side chain of the molecular chain segment, or at both the end and the side chain.

[0074] In an optional embodiment, the styrene-terminated phenolic resin has a structure shown in formula (4):

[0075]

[0076] Wherein, R is a divalent organic group, and n1 is an integer from 1 to 30.

[0077] In an optional embodiment, the divalent organic group is at least one of an alkylene group, a dicyclopentadienyl group, a substituted or unsubstituted arylene group, a combination of an alkylene group and an arylene group (also called an aralkylene group or an alkylarylene group), and an aromatic heterocyclic group.

[0078] In an optional embodiment, the alkylene group is a straight chain alkyl group or a branched chain alkyl group containing 1 to 4 carbon atoms; the arylene group is at least one of phenyl, naphthyl, anthracenyl, biphenyl, and fluorenyl; the aromatic heterocyclic group is at least one of a pyridine ring, a pyrrole ring, a pyrazole ring, a pyrimidine ring, a pyrazine ring, a pyridazine ring, a thiophene ring, and a furan ring. In an optional embodiment, the R group can be exemplified but not limited to:

[0079]

[0080] In an optional embodiment, R is at least one of a methylene group, a biscyclopentadienyl group, and a substituted or unsubstituted arylene group, and n1 is an integer from 1 to 10.

[0081] In an optional embodiment, the styrene-terminated phenolic resin may be any one or more commercially available products, homemade products, or combinations thereof. In an optional embodiment, the styrene-terminated phenolic resin is a product obtained by reacting 4-vinylbenzyl chloride with a phenolic resin in the presence of sodium hydroxide and tetrabutylammonium iodide, or by reacting 4-vinylbenzyl chloride with a phenolic resin in the presence of sodium alcoholate (e.g., sodium methoxide or sodium ethoxide). Specific examples of styrene-terminated phenolic resins include, but are not limited to, styrene-terminated dicyclopentadiene phenolic resins (e.g., KPU-6270 purchased from Kolon Industries) (R is a divalent dicyclopentadiene group, n1 is an integer from 1 to 10), styrene-terminated alkyl phenolic resins (R is a methylene group, n1 is an integer from 1 to 10), and styrene-terminated biphenyl phenolic resins (R is 4,4'-dimethylene biphenyl, n1 is an integer from 1 to 10).

[0082] In an optional embodiment, compared to 100 parts by weight of the copolymer of phenylvinylsilane and alkenyl compound, the resin composition may further include 0.1 to 40 parts by weight of polyolefin resin, preferably 5 to 30 parts by weight. In an optional embodiment, the polyolefin resin is 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, and is not limited thereto. In another optional embodiment, the resin composition does not include a polyolefin resin.

[0083] In an optional embodiment, the polyolefin resin includes at least one of an unsaturated polyolefin resin and a hydrogenated unsaturated polyolefin resin; the unsaturated polyolefin resin of the present invention can be any one or more polyolefin resins containing unsaturated carbon-carbon double bonds suitable for making prepregs, resin films, laminates, printed circuit boards or cured insulators. Specific examples include but are not limited to styrene-butadiene-divinylbenzene terpolymers, maleic anhydride-added styrene-butadiene polymers, maleic anhydride-added polybutadiene, styrene-butadiene-styrene block polymers, vinyl-polybutadiene-urethane oligomers, styrene-butadiene copolymers, styrene-isoprene copolymers, polybutadiene, ethylene propylene diene rubber, methyl styrene homopolymers, petroleum resins and cyclic olefin copolymers. The hydrogenated unsaturated polyolefin resin of the present invention is obtained by hydrogenating an unsaturated polyolefin resin, and can be any one or more hydrogenated unsaturated polyolefin resins containing no unsaturated carbon-carbon double bonds suitable for making prepregs, resin films, laminates, printed circuit boards or cured insulators. Specific examples include but are not limited to at least one of hydrogenated styrene-butadiene copolymers, hydrogenated styrene-butadiene-styrene block polymers and hydrogenated styrene-isoprene copolymers.

[0084] In an optional embodiment, unless otherwise specified, the resin composition further comprises at least one of vinyl-containing polyphenylene ether resin, maleimide resin, maleimide triazine resin, small molecule vinyl-containing resin, small molecule vinyl-containing resin prepolymer, styrene maleic anhydride resin, epoxy resin, phenolic resin, benzoxazine resin, cyanate resin, polyester resin, polyamide resin, and polyimide resin.

[0085] For example, in one embodiment, the vinyl-containing polyphenylene ether resin may include various polyphenylene ether resins whose terminals are modified by vinyl or allyl groups, such as vinyl benzyl polyphenylene ether resins, or the vinyl-containing polyphenylene ether resin may be a polyphenylene ether resin containing (meth)acrylate. For example, the vinyl-containing polyphenylene ether resin includes vinyl benzyl biphenyl polyphenylene ether resin, methacrylate polyphenylene ether resin, vinyl benzyl bisphenol A polyphenylene ether resin, vinyl-containing extended chain polyphenylene ether resin or a combination thereof, and is not limited thereto. Unless otherwise specified, the amount of the vinyl-containing polyphenylene ether resin is not particularly limited.

[0086] For example, in one embodiment, the aforementioned vinyl-containing polyphenylene ether resin may include various types of vinyl-containing polyphenylene ether resins known in the art. The vinyl-containing polyphenylene ether resins suitable for the present invention are not particularly limited, and may be any one or more commercially available products, homemade products, or combinations thereof. In certain embodiments, any one or more of the following vinyl-containing polyphenylene ether resins may be used: vinyl-containing benzyl biphenyl polyphenylene ether resins (e.g., OPE-2st, available from Mitsubishi Gas Chemical Co., Ltd.), methacrylate-containing polyphenylene ether resins (e.g., SA9000, available from Sabic), vinyl-containing benzyl bisphenol A polyphenylene ether resins, vinyl-containing extended chain polyphenylene ether resins, or combinations thereof. The aforementioned vinyl-containing extended chain polyphenylene ether resins may include various types of polyphenylene ether resins in U.S. patent application publication number 2016 / 0185904A1, the entire contents of which are incorporated herein by reference.

[0087] For example, in one embodiment, the maleimide resin used in the present invention refers to a compound or mixture having one or more maleimide functional groups in the molecule. Unless otherwise specified, the maleimide resin used in the present invention is not particularly limited and can be any one or more maleimide resins suitable for making prepregs, resin films, laminates, printed circuit boards or cured insulators. Specific examples include, but are not limited to, 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide oligomers, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, 2,3-dimethylbenzene maleimide, 2,6-dimethylbenzene maleimide, N-phenyl maleimide, maleimide resins containing aliphatic long chain structures, or combinations thereof. In addition, unless otherwise specified, the maleimide resin described in the present invention also includes prepolymers of the aforementioned resins, such as prepolymers of diallyl compounds and maleimide resins, prepolymers of polyfunctional amines (including greater than or equal to two amino groups) and maleimide resins, or prepolymers of acidic phenol compounds and maleimide resins, etc., but are not limited thereto.

[0088] For example, the maleimide resin may be a maleimide resin produced by Daiwakasei Corporation under the trade names of BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000H, BMI-5000, BMI-5100, BMI-7000, and BMI-7000H, or a maleimide resin produced by KI Chemical Co., Ltd. under the trade names of BMI-70, BMI-80, etc.

[0089] For example, the maleimide resin containing a long chain aliphatic structure may be a maleimide resin produced by a designer molecular company under the trade names of BMI-689, BMI-1400, BMI-1500, BMI-1700, BMI-2500, BMI-3000, BMI-5000 and BMI-6000. For example, the maleimide resin containing a long chain aliphatic structure may have at least one maleimide functional group connected to a substituted or unsubstituted long chain aliphatic group. The long chain aliphatic group may be an aliphatic group with a carbon number of C5 to C50, such as a carbon number of C10 to C50, C20 to C50, C30 to C50, C20 to C40 or C30 to C40, but is not limited thereto.

[0090] For example, in one embodiment, the maleimide triazine resin of the present invention is not particularly limited, and can be any one or more maleimide triazine resins suitable for semi-cured sheets, resin films, laminates, printed circuit boards or cured insulators. For example, the maleimide triazine resin can be obtained by polymerizing a cyanate resin and a maleimide resin. The maleimide triazine resin can be obtained by, for example, but not limited to, polymerizing a bisphenol A cyanate resin and a maleimide resin, polymerizing a bisphenol F cyanate resin and a maleimide resin, polymerizing a phenol novolac cyanate resin and a maleimide resin, or polymerizing a dicyclopentadiene-containing cyanate resin and a maleimide resin. For example, the maleimide triazine resin can be obtained by polymerizing a cyanate resin and a maleimide resin in any molar ratio. For example, relative to 1 mole of maleimide resin, the cyanate resin can be 1 to 10 moles. For example, but not limited to, the cyanate resin is present in an amount of 1, 2, 4 or 6 moles relative to 1 mole of the maleimide resin.

[0091] For example, in one embodiment, the small molecule vinyl resin refers to a vinyl compound having a molecular weight less than or equal to 1,000, preferably a molecular weight between 100 and 900, and more preferably a molecular weight between 100 and 800. For example, the small molecule vinyl resin includes, but is not limited to, styrene, divinylbenzene, bis(vinylbenzyl)ether, 1,2,4-trivinylcyclohexane (1,2,4-trivinylcyclohexane, TVCH), bis(vinylphenyl)ethane (BVPE), di(vinylphenyl)hexane, bisvinylphenyl dimethylene ether, bisvinylphenyl dimethylene benzene, triallyl isocyanurate (TAIC) and / or triallyl cyanurate (TAC).

[0092] For example, in one embodiment, the small molecule vinyl resin prepolymer may include a styrene prepolymer, a divinylbenzene prepolymer, a di(vinylbenzyl)ether prepolymer, a 1,2,4-trivinylcyclohexane prepolymer, a di(vinylphenyl)ethane prepolymer, a di(vinylphenyl)hexane prepolymer, a divinylphenyl dimethylene ether prepolymer, a divinylphenyl dimethylene benzene prepolymer, a triallyl isocyanurate prepolymer, a triallyl cyanurate prepolymer or a combination thereof, but is not limited thereto. For example, in one embodiment, the styrene prepolymer represents a styrene content greater than or equal to 50 wt %, and for example, the styrene content in the styrene prepolymer is between 50 wt % and 99 wt %, and the content of the second monomer unit in the styrene prepolymer is less than or equal to 49 wt %, for example, between 1 wt % and 49 wt %. For example, in one embodiment, the styrene prepolymer includes 60 wt % of styrene monomer units, 30 wt % of divinylbenzene monomer units and 10 wt % of ethyl styrene monomer units. In yet another embodiment, the divinylbenzene prepolymer includes 60 wt % of divinylbenzene monomer units, 30 wt % of ethylstyrene monomer units, and 10 wt % of styrene monomer units.

[0093] For example, in one embodiment, in the styrene maleic anhydride resin used in the present invention, the ratio of styrene (S) to maleic anhydride (MA) may be 1:1, 2:1, 3:1, 4:1, 6:1 or 8:1, such as but not limited to styrene maleic anhydride copolymers sold by Cray Valley under the trade names SMA-1000, SMA-2000, SMA-3000, EF-30, EF-40, EF-60 and EF-80, or styrene maleic anhydride copolymers sold by Polyscope under the trade names C400, C500, C700, C900, etc. In addition, the styrene maleic anhydride resin may also be an esterified styrene maleic anhydride copolymer, such as esterified styrene maleic anhydride copolymers purchased from Cray Valley under the trade names SMA1440, SMA17352, SMA2625, SMA3840 and SMA31890. If not otherwise specified, the above styrene maleic anhydride resins may be added to the resin composition of the present invention independently or in combination.

[0094] For example, in one embodiment, the epoxy resin used in the present invention can be various epoxy resins known in the art, including but not limited to bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD ​​epoxy resin, novolac epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, multifunctional novolac epoxy resin, dicyclopentadiene (DCPD) epoxy resin, phosphorus-containing epoxy resin, p-xylene epoxy resin, naphthalene epoxy resin (e.g., naphthol epoxy resin), benzofuran epoxy resin, and isocyanate-modified epoxy resin. The novolac epoxy resin may be phenol novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, biphenyl novolac epoxy resin, phenolbenzaldehyde epoxy resin, phenol aralkyl novolac epoxy resin or o-cresol novolac epoxy resin; the phosphorus-containing epoxy resin may be DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) epoxy resin, DOPO-HQ epoxy resin or a combination thereof.The aforementioned DOPO epoxy resin may be selected from one or more of DOPO-containing phenolic novolac epoxy resin, DOPO-containing cresol novolac epoxy resin and DOPO-containing bisphenol-A novolac epoxy resin; the aforementioned DOPO-HQ epoxy resin may be selected from at least one of DOPO-HQ-containing phenolic novolac epoxy resin, DOPO-HQ-containing cresol novolac epoxy resin and DOPO-HQ-containing bisphenol-A novolac epoxy resin.

[0095] For example, in one embodiment, the phenolic resin of the present invention may be a monofunctional, polyfunctional (including greater than or equal to two phenolic hydroxyl groups) phenolic resin or a combination thereof. The type of the above phenolic resin is not particularly limited, and all kinds of phenolic resins currently used in the industry are within the scope of phenolic resins applicable to the present invention. Preferably, the phenolic resin is selected from phenoxy resin, phenolic resin or a combination thereof.

[0096] For example, in one embodiment, the benzoxazine resin of the present invention may be a bisphenol A-type benzoxazine resin, a bisphenol F-type benzoxazine resin, a phenolphthalein-type benzoxazine resin, a dicyclopentadiene benzoxazine resin, or a phosphorus-containing benzoxazine resin, such as LZ-8270 (phenolphthalein-type benzoxazine resin), LZ-8280 (bisphenol F-type benzoxazine resin), LZ-8290 (bisphenol A-type benzoxazine resin) produced by Huntsman, or HFB-2006M produced by Showa Polymer Corporation.

[0097] For example, in one embodiment, the cyanate resin described in the present invention may be various types of cyanate resins known in the art, wherein the cyanate resin includes but is not limited to a cyanate resin having an Ar-OC≡N structure (wherein Ar is an aromatic group, such as benzene, naphthalene or anthracene), a phenol novolac cyanate resin, a bisphenol A cyanate resin, a bisphenol A novolac cyanate resin, a bisphenol F cyanate resin, a bisphenol F novolac cyanate resin, a cyanate resin containing a dicyclopentadiene structure, a cyanate resin containing a naphthalene ring structure, a phenolphthalein cyanate resin or a combination thereof. For example, examples of cyanate resins include, but are not limited to, cyanate resins produced by Lonza under the trade names of Primaset PT-15, PT-30S, PT-60S, BA-200, BA-230S, BA-3000S, BTP-2500, BTP-6020S, DT-4000, DT-7000, ULL950S, HTL-300, CE-320, LVT-50, LeCy, etc.

[0098] For example, in one embodiment, the polyester resin of the present invention is formed by esterification of an aromatic compound having a dicarboxylic acid group and an aromatic compound having a dihydroxyl group, such as but not limited to HPC-8000, HPC-8150 or HPC-8200 available from Dainippon Ink Chemicals.

[0099] For example, in one embodiment, the polyamide resin of the present invention may be any type of polyamide resin known in the art, including but not limited to various commercially available polyamide resin products.

[0100] For example, in one embodiment, the polyimide resin of the present invention may be any type of polyimide resin known in the art, including but not limited to various commercially available polyimide resin products.

[0101] Unless otherwise specified, the ratio between the copolymer and the resin additive is not particularly limited.

[0102] In an optional embodiment, the resin composition further comprises at least one of an amine curing agent, a flame retardant, an inorganic filler, a curing accelerator, an inhibitor, a colorant, a solvent, a toughening agent, and a silane coupling agent.

[0103] For example, in one embodiment, the amine curing agent of the present invention may be at least one of dicyandiamide, diaminodiphenyl sulfone, diaminodiphenylmethane, diaminodiphenyl ether, and diaminodiphenyl sulfide, but is not limited thereto.

[0104] For example, in one embodiment, the flame retardant of the present invention can be any one or more flame retardants suitable for the production of prepregs, resin films, laminates, printed circuit boards or cured insulators. Specific examples include, but are not limited to, phosphorus-containing flame retardants, such as at least one, a combination of two or more selected from the following groups: ammonium polyphosphate, hydroquinone bis-(diphenylphosphate), bisphenol A bis-(diphenylphosphate), tri(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl) phosphate, trimethyl phosphate (TMP), dimethyl methylphosphonate (DMMP), resorcinol bis-(xylyl phosphate) The invention can be selected from the group consisting of at least one of dixylenylphosphate (RDXP), such as PX-200, PX-201, PX-202 and other commercial products), phosphazene (such as SPB-100, SPH-100, SPV-100 and other commercial products), melamine polyphosphate, DOPO and its derivatives or resins, diphenylphosphine oxide (DPPO) and its derivatives or resins, melamine cyanurate, tri-hydroxy ethylisocyanurate, and aluminum phosphinate (such as OP-930, OP-935 and other products).

[0105] For example, the flame retardant used in the present invention can be a DPPO compound (such as a bis-DPPO compound), a DOPO compound (such as a bis-DOPO compound), a DOPO resin (such as DOPO-HQ, DOPO-NQ, DOPO-PN, DOPO-BPN), a DOPO-bonded epoxy resin, etc., wherein DOPO-PN is a DOPO phenol novolac compound, and DOPO-BPN can be a bisphenol novolac compound such as DOPO-BPAN (DOPO-bisphenol Anovolac), DOPO-BPFN (DOPO-bisphenol F novolac) or DOPO-BPSN (DOPO-bisphenol Snovolac).

[0106] For example, in one embodiment, the inorganic filler of the present invention can be any one or more fillers suitable for making resin films, prepregs, laminates, printed circuit boards or cured insulators, and specific examples include but are not limited to: silicon dioxide (molten, non-molten, porous or hollow), aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, mica, boehmite (boehmite, AlOOH), calcined talc, talc, silicon nitride or calcined kaolin. In addition, the aforementioned inorganic filler can be spherical, fibrous, plate-like, granular, flaky or needle-like, and can be selectively pretreated with a silane coupling agent.

[0107] In one embodiment, for example, the curing accelerator (including curing initiator) of the present invention may include catalysts such as Lewis base or Lewis acid. Wherein, Lewis base may include one or more of imidazole, boron trifluoride amine complex, ethyltriphenyl phosphonium chloride, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MI), triphenylphosphine (TPP) and 4-dimethylaminopyridine (DMAP). Lewis acid may include metal salt compounds, such as metal salt compounds such as manganese, iron, cobalt, nickel, copper, zinc, such as metal catalysts such as zinc octoate and cobalt octoate. The curing accelerator also includes a curing initiator (i.e., an initiator), such as a peroxide that can generate free radicals. The curing initiator includes, but is not limited to: 2,3-dimethyl-2,3-diphenylbutane, diisopropyl peroxide, tert-butyl perbenzoate, dibenzoyl peroxide (BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne (25B), bis(tert-butylperoxyisopropyl)benzene, azobisisobutyronitrile, or a combination thereof.

[0108] In one embodiment, for example, the polymerization inhibitor of the present invention is not particularly limited, for example, it can be various types of polymerization inhibitors known in the art, including but not limited to various commercially available polymerization inhibitor products. For example, the above-mentioned polymerization inhibitor can include but is not limited to 1,1-diphenyl-2-trinitrophenylhydrazine, methacrylonitrile, dithioester, nitrogen oxide stable free radical, triphenylmethyl free radical, metal ion free radical, sulfur free radical, hydroquinone, p-methoxyphenol, p-benzoquinone, phenothiazine, β-phenylnaphthylamine, p-tert-butylcatechol, methylene blue, 4,4'-butylenebis(6-tert-butyl-3-methylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol) or a combination thereof.

[0109] For example, the above-mentioned nitrogen oxide stable free radicals may include but are not limited to nitrogen oxide free radicals from cyclic hydroxylamines such as 2,2,6,6-substituted-1-piperidinyloxy free radicals or 2,2,5,5-substituted-1-pyrrolidinyloxy free radicals. As a substituent, an alkyl group with a carbon number of 4 or less, such as methyl or ethyl, is preferred. As specific nitrogen oxide free radical compounds, 2,2,6,6-tetramethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetraethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetramethyl-4-oxo-1-piperidinyloxy free radicals, 2,2,5,5-tetramethyl-1-pyrrolidinyloxy free radicals, 1,1,3,3-tetramethyl-2-isoindolinyloxy free radicals, N,N-di-tert-butylamineoxy free radicals, etc. can be cited. Stable free radicals such as galvinoxyl free radicals can also be used instead of nitrogen oxide free radicals.

[0110] The polymerization inhibitor applicable to the resin composition of the present invention may also be a product derived from the substitution of hydrogen atoms or atomic groups in the polymerization inhibitor by other atoms or atomic groups, for example, a product derived from the substitution of hydrogen atoms in the polymerization inhibitor by atomic groups such as amino, hydroxyl, ketocarbonyl, etc.

[0111] In one embodiment, for example, the coloring agent suitable for the present invention may include, but is not limited to, dyes or pigments.

[0112] In one embodiment, for example, the main effect of adding a solvent is to change the solid content of the resin composition and adjust the viscosity of the resin composition. For example, the solvent may include but is not limited to methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, propylene glycol methyl ether and other solvents or their mixed solvents. In some embodiments, the solvent added to the resin composition can be volatilized and removed during the processing of the resin composition into a prepreg or a resin film, so that the insulating layer of the prepreg or the resin film does not contain a solvent or only contains a trace amount of solvent less than or equal to 3wt% (i.e., 3% by weight), so the presence or absence of a solvent in the resin composition does not affect the characteristics of the product.

[0113] In one embodiment, for example, the main function of adding a toughening agent is to improve the toughness of the resin composition. The toughening agent may include but is not limited to carboxyl-terminated butadiene acrylonitrile rubber (CTBN), core-shell rubber, and other compounds or combinations thereof.

[0114] In one embodiment, for example, the silane coupling agent used in the present invention may include a silane compound (such as but not limited to a siloxane compound), which can be divided into amino silane compounds, epoxy silane compounds, vinyl silane compounds, acrylate silane compounds, methacrylate silane compounds, hydroxy silane compounds, isocyanate silane compounds, methacryloxy silane compounds and acryloxy silane compounds according to the type of functional group.

[0115] In a second aspect, the present invention provides a product, which is made of the above-mentioned resin composition, and the product includes but is not limited to a prepreg, a resin film, a laminate, a printed circuit board or a cured insulator.

[0116] For example, the resin composition of each embodiment of the present invention can be made into a semi-cured sheet, which includes a reinforcing material and a layered object disposed on the reinforcing material. The layered object is obtained by heating the aforementioned resin composition at a high temperature to form a semi-cured state (B-stage). The baking temperature for making the semi-cured sheet can be between 100°C and 200°C. The reinforcing material can be any one of a fiber material, a woven fabric, and a non-woven fabric, and the woven fabric preferably includes a glass fiber cloth. The type of glass fiber cloth is not particularly limited, and can be a commercially available glass fiber cloth that can be used for various printed circuit boards, such as E-type glass cloth, D-type glass cloth, S-type glass cloth, T-type glass cloth, L-type glass cloth or Q-type glass cloth, wherein the types of fibers include yarns and rovings, etc., and the form can include open fibers or unopen fibers. The aforementioned non-woven fabric preferably includes a liquid crystal resin non-woven fabric, such as a polyester non-woven fabric, a polyurethane non-woven fabric, etc., and is not limited thereto. The aforementioned woven fabric may also include a liquid crystal resin woven fabric, such as a polyester woven fabric or a polyurethane woven fabric, etc., and is not limited thereto. The reinforcing material can increase the mechanical strength of the prepreg. In a preferred embodiment, the reinforcing material can also be selectively pretreated with a silane coupling agent. The prepreg is subsequently heated and cured (C-stage) to form an insulating layer.

[0117] For example, the resin composition of each embodiment of the present invention can be made into a resin film, which is obtained by semi-curing the aforementioned resin composition after baking and heating. The resin composition can be selectively coated on a polyethylene terephthalate film (PET film), a polyimide film (PI film), a copper foil or a copper foil with adhesive, and then semi-cured after baking and heating, so that the resin composition forms a resin film.

[0118] For example, the resin composition of each embodiment of the present invention can be made into a laminate, which includes at least two metal foils and an insulating layer disposed between the metal foils. The insulating layer can be obtained by curing (C-stage) the resin composition under high temperature and high pressure conditions, wherein the suitable curing temperature can be between 180°C and 250°C, preferably between 200°C and 230°C, and the curing time is 90 to 180 minutes, preferably 120 to 150 minutes. The insulating layer can be formed by curing (C-stage) the prepreg or resin film. The metal foil can include copper, aluminum, nickel, platinum, silver, gold or their alloys, for example, the metal foil can be copper foil.

[0119] Preferably, the aforementioned laminate is a copper clad laminate (CCL).

[0120] In addition, the aforementioned laminate can be further processed through a circuit process to form a circuit board, such as a printed circuit board. One method of making the printed circuit board of the present invention can be to use a double-sided copper-clad laminate (such as product EM-890, which can be purchased from Taiwan Optoelectronics Materials) with a thickness of 28 mils and 0.5 ounces of HVLP (hyper very low profile) copper foil, and then electroplating after drilling to form electrical conduction between the upper copper foil and the bottom copper foil. The upper copper foil and the bottom copper foil are then etched to form an inner layer circuit. The inner layer circuit is then browned and roughened to form a concave-convex structure on the surface to increase the roughness. Then, the copper foil, the aforementioned semi-cured sheet, the aforementioned inner layer circuit board, the aforementioned semi-cured sheet, and the copper foil are stacked in sequence, and then a vacuum laminating device is used to heat for 90 to 180 minutes at a temperature of 180°C to 250°C to cure the insulating layer material of the semi-cured sheet. Next, various circuit board processing techniques known in the art such as blackening, drilling, and copper plating are performed on the copper foil on the outermost surface to obtain a printed circuit board.

[0121] For example, the resin composition of each embodiment of the present invention can be made into a cured insulator, which includes the aforementioned resin composition in a cured state, the aforementioned resin composition in a cured state containing a reinforcing material, or a combination thereof. In one embodiment, the present invention provides a method for preparing a cured insulator, comprising: directly curing the aforementioned resin composition or curing the aforementioned resin composition through a multiple curing process. The multiple curing refers to curing greater than or equal to twice. For example, the aforementioned resin composition can be semi-cured first to obtain the aforementioned resin composition in a semi-cured state, and then the aforementioned resin composition in a semi-cured state can be further cured to obtain the aforementioned resin composition in a cured state. The curing is preferably heat curing.

[0122] In one embodiment, the heating is baking heating, and the semi-curing of the aforementioned resin composition is heating to a semi-curing temperature, which may be between 100°C and 200°C. In one embodiment, the direct curing of the aforementioned resin composition or curing of the aforementioned resin composition in a semi-cured state is heating to a curing temperature, which may be between 180°C and 250°C, preferably between 200°C and 230°C, and the curing time is 90 to 180 minutes, preferably 120 to 150 minutes. In one embodiment, the curing includes applying pressure to the aforementioned resin composition or the aforementioned resin composition in a semi-cured state.

[0123] In one embodiment, the cured insulator comprises the aforementioned resin composition in a cured state, which can be obtained by curing the aforementioned resin film. In one embodiment, the cured insulator comprises the aforementioned resin composition in a cured state containing a reinforcing material, which can be obtained by curing the aforementioned prepreg.

[0124] In one embodiment, the method for preparing the cured insulator further comprises a molding method. For example, the resin composition or the semi-cured resin composition can be placed in a mold, and the resin composition or the semi-cured resin composition can be formed and cured in the mold at a curing temperature and a certain pressure, thereby obtaining a cured insulator of a specific shape.

[0125] In one embodiment, the cured insulator is an insulating layer having a surface free of metal obtained by removing a surface metal foil from the aforementioned laminate or the aforementioned printed circuit board.

[0126] Preferably, the resin composition or its product provided by the present invention can be improved in one or more aspects such as glass transition temperature, copper foil tensile force, dielectric constant, dielectric loss, thermal expansion rate, thermal expansion coefficient or PCT heat resistance.

[0127] In an optional embodiment, the glass transition temperature of the article measured according to IPC-TM-650 2.4.24.4 method is greater than or equal to 220°C, for example, greater than or equal to 221°C, and for example, between 221°C and 260°C;

[0128] In an optional embodiment, the glass transition temperature of the article measured with reference to the method described in IPC-TM-650 2.4.24.5 is greater than or equal to 200°C, for example, greater than or equal to 201°C, and for example, between 201°C and 230°C;

[0129] In an optional embodiment, the copper foil tensile force of the product measured with reference to IPC-TM-650 2.4.8 method is greater than or equal to 2.00 lb / in, for example, between 2.00 lb / in and 3.00 lb / in;

[0130] In an optional embodiment, the Z-axis thermal expansion coefficient of the product measured with reference to IPC-TM-650 2.4.24.5 method is less than or equal to 1.4%, for example, between 0.70% and 1.40%;

[0131] In an optional embodiment, the X and Y axis thermal expansion coefficients of the product measured according to IPC-TM-650 2.4.24.5 method are less than or equal to 11.0 ppm / °C, for example, between 7.5 ppm / °C and 11.0 ppm / °C;

[0132] In an optional embodiment, after performing a pressure cooking test according to the method described in IPC-TM-650 2.6.16.1 for 5 hours, a heat resistance test according to the method described in IPC-TM-650 2.4.23 is performed and no panel explosion occurs.

[0133] In an optional embodiment, the dielectric constant of the product measured at a frequency of 10 GHz with reference to the JIS C2565 method is less than or equal to 3.40, for example, between 3.20 and 3.40;

[0134] And / or, the dielectric loss of the product measured at a frequency of 10 GHz with reference to JIS C2565 method is less than or equal to 0.00300, for example, between 0.00240 and 0.00300.

[0135] The present invention is further described in detail below in conjunction with specific embodiments. The following specific embodiments are merely illustrative in nature and should not be construed as limiting the scope of protection claimed by the present invention and its uses.

[0136] The following raw materials were used to prepare the preparation examples of the present invention and the comparative preparation examples according to the amounts in Table 1, and the resin compositions of the embodiments of the present invention and the comparative examples of the present invention were prepared according to the amounts in Tables 4 to 8, and were further made into various test samples or products.

[0137] The chemical raw materials used in the preparation examples, embodiments and comparative examples of the present invention are as follows:

[0138] Phenyl trivinyl silane: purchased from Suzhou Silco, the structural formula is:

[0139] Diphenyl divinyl silane: purchased from Suzhou Silsuo, the structural formula is:

[0141] Methyltrivinylsilane: commercially available from any source.

[0142] Tetraphenyldivinyldisiloxane: commercially available from any source.

[0143] 2,4-Diphenyl-4-methyl-1-pentene: purchased from Aladdin,

[0144] The structural formula is:

[0145] 2,4-Diphenyl-3,4-dimethyl-1-hexene: synthesized according to the method of Synthesis Example 1,

[0146] The structural formula is:

[0147] 2,4-Di(p-methoxy)phenyl-4-methyl-1-pentene: synthesized according to the method of Synthesis Example 2,

[0148] The structural formula is:

[0149] 1,4-Naphthoquinone: purchased from Aladdin.

[0150] n-Dodecyl mercaptan: purchased from Aladdin.

[0151] KPU-6270: Styrene-terminated dicyclopentadiene phenolic resin, purchased from Kolon Industries, with the structural formula:

[0152]

[0153] Styrene-terminated alkyl phenolic resin: synthesized according to the method of Synthesis Example 3, the structural formula is:

[0154]

[0155]

[0156] Styrene-terminated biphenyl phenolic resin: synthesized according to the method of Synthesis Example 4, the structural formula is:

[0157]

[0158] H1051: hydrogenated styrene-butadiene-styrene triblock copolymer (SEBS), purchased from Asahi Kasei Corporation.

[0159] MD1648: hydrogenated styrene-butadiene-styrene triblock copolymer (SEBS), purchased from Kraton.

[0160] SBS-C: styrene-butadiene-styrene triblock copolymer, purchased from Nippon Soda Co.

[0161] EBT-4045M: EPDM rubber, purchased from Sinopec Mitsui Chemicals.

[0162] Ricon 100: styrene-butadiene copolymer, available from Cray Valley Corporation.

[0163] Ricon 184MA6: maleic anhydride added styrene-butadiene polymer, available from Cray Valley Company.

[0164] Ricon 257: styrene-butadiene-divinylbenzene terpolymer, available from Cray Valley Corporation.

[0165] SA9000: terminal dimethacrylate polyphenylene ether resin, purchased from Sabic.

[0166] OPE-2st 1200: terminal bisvinyl benzyl polyphenylene ether resin, purchased from Sabic.

[0167] SC-2050SMJ: spherical silica with the surface treated with a silane coupling agent, purchased from Admatechs.

[0168] 25B: 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, purchased from NOF Corporation.

[0169] Butanone: commercially available from any source.

[0170] Toluene: purchased from Qiangdi.

[0171] Synthesis example 1

[0172] This synthesis example provides a method for synthesizing 2,4-diphenyl-3,4-dimethyl-1-hexene, comprising the following steps:

[0173] 20 g of but-1-en-2-ylbenzene (purchased from Aladdin) and 10 g of toluene were added to the flask and stirred to mix evenly. Then 0.2 g of p-toluenesulfonic acid monohydrate was added and the flask was heated with N 2 The mixture was replaced and reacted at 20°C for 20 hours. 2 mL of pure water was added to stop the reaction. The reaction mixture was diluted with 20 g of ethyl acetate. The organic phase was washed with pure water to remove impurities, dried, filtered, and the solvent was removed by rotary evaporation to obtain 2,4-diphenyl-3,4-dimethyl-1-hexene.

[0174] Synthesis example 2

[0175] This synthesis example provides a method for synthesizing 2,4-di(p-methoxy)phenyl-4-methyl-1-pentene, comprising the following steps:

[0176] The difference from Synthesis Example 1 is that 20 g of 1-isopropenyl-4-methoxybenzene (purchased from Aladdin) is used to replace but-1-en-2-ylbenzene to obtain 2,4-di(p-methoxy)phenyl-4-methyl-1-pentene.

[0177] Synthesis example 3

[0178] This synthesis example provides a method for synthesizing a styrene-terminated alkyl phenolic resin, comprising the following steps:

[0179] 105g (containing 1.0mol of phenolic hydroxyl groups) alkyl phenolic resin (TD-2090, R group is methylene, hydroxyl equivalent 105g / eq, purchased from DIC), 1.05mol 4-vinylbenzyl chloride and 150g toluene were put into a reaction tank device, the temperature was set at 70°C, stirred for reaction for 6 hours, 1.05mol of sodium hydroxide and 0.07mol of tetrabutylammonium iodide were added and the reaction was continued for 4 hours. After the reaction, the reaction mixture was washed with methanol and distilled water and dried to obtain a styrene-terminated alkyl phenolic resin with R group being methylene.

[0180] Synthesis example 4

[0181] This synthesis example provides a method for synthesizing a styrene-terminated biphenyl phenolic resin, comprising the following steps:

[0182] The difference from Preparation Example 3 is that 220 g (containing 1.0 mol of phenolic hydroxyl group) of biphenyl-type phenol-formaldehyde resin (BPNH9781, R group is 4,4'-dimethylene biphenyl, hydroxyl equivalent 215-225 g / eq, purchased from Jiashengde) is used to replace the alkyl-type phenol-formaldehyde resin to obtain a styrene-terminated biphenyl-type phenol-formaldehyde resin whose R group is 4,4'-dimethylene biphenyl.

[0183] Preparation of copolymers

[0184] The weight parts of the raw materials in each preparation example and comparative preparation example of the copolymer prepared by the present invention are specifically shown in Table 1. The blank in the table represents "0".

[0185] Table 1 Raw material composition of preparation examples and comparative preparation examples

[0186]

[0187] Preparation Example 1

[0188] This preparation example provides a method for preparing a copolymer, comprising the following steps:

[0189] (1) Under nitrogen protection, 98 parts by weight of phenyltrivinylsilane, 2 parts by weight of 2,4-diphenyl-4-methyl-1-pentene, 0.5 parts by weight of 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne (25B for short), and 40 parts by weight of toluene were added to a three-necked flask, heated to 120° C., stirred for reaction for 5 hours, and cooled to room temperature after the reaction was completed to obtain a crude reaction product 1.

[0190] (2) The crude product 1 is slowly poured into anhydrous ethanol under stirring to precipitate a white precipitate, which is filtered and washed with anhydrous ethanol to obtain a white solid 1. The obtained white solid 1 is placed in a vacuum drying oven at 50° C. to 70° C. for 6 to 10 hours, and the residual solvent is removed to obtain a white solid 2 (i.e., product 2), which is a copolymer 1, wherein the content of the structural unit formed by phenyltrivinylsilane is 98 mol%.

[0191] Preparation Example 2

[0192] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 95 parts by weight of phenyltrivinylsilane and 5 parts by weight of 2,4-diphenyl-4-methyl-1-pentene are added to obtain a copolymer 2, in which the content of the structural unit formed by phenyltrivinylsilane is 94 mol%.

[0193] Preparation Example 3

[0194] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 90 parts by weight of phenyltrivinylsilane and 10 parts by weight of 2,4-diphenyl-4-methyl-1-pentene are added to obtain a copolymer 3, in which the content of the structural unit formed by phenyltrivinylsilane is 92 mol%.

[0195] Preparation Example 4

[0196] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 85 parts by weight of phenyltrivinylsilane and 15 parts by weight of 2,4-diphenyl-4-methyl-1-pentene are added to obtain copolymer 4, in which the content of the structural unit formed by phenyltrivinylsilane is 88 mol%.

[0197] Preparation Example 5

[0198] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 80 parts by weight of phenyltrivinylsilane and 20 parts by weight of 2,4-diphenyl-4-methyl-1-pentene are added to obtain a copolymer 5, in which the content of the structural unit formed by phenyltrivinylsilane is 84 mol%.

[0199] Preparation Example 6

[0200] This preparation example provides a preparation method of a copolymer, which is different from Preparation Example 1 in that: 60 parts by weight of phenyltrivinylsilane and 30 parts by weight of diphenyldivinylsilane are used instead of 98 parts by weight of phenyltrivinylsilane, and 10 parts by weight of 2,4-diphenyl-4-methyl-1-pentene are used instead of 2 parts by weight of 2,4-diphenyl-4-methyl-1-pentene to obtain copolymer 6, in which the content of the structural unit formed by phenyltrivinylsilane and diphenyldivinylsilane is 91 mol%.

[0201] Preparation Example 7

[0202] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that diphenyldivinylsilane is used instead of phenyltrivinylsilane to obtain copolymer 7, in which the content of the structural unit formed by diphenyldivinylsilane is 90 mol%.

[0203] Preparation Example 8

[0204] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that 2,4-diphenyl-3,4-dimethyl-1-hexene prepared in Preparation Example 1 is used instead of 2,4-diphenyl-4-methyl-1-pentene to obtain copolymer 8, and the content of the structural unit formed by phenyltrivinylsilane is 92 mol%.

[0205] Preparation Example 9

[0206] This preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that 2,4-di(p-methoxy)phenyl-4-methyl-1-pentene prepared in Preparation Example 2 is used instead of 2,4-diphenyl-4-methyl-1-pentene to obtain copolymer 9, in which the content of the structural unit formed by phenyltrivinylsilane is 93 mol%.

[0207] Comparative Preparation Example 1

[0208] This comparative example preparation provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 100 parts by weight of phenyltrivinylsilane is added and 2,4-diphenyl-4-methyl-1-pentene is not added to obtain comparative self-polymer 1.

[0209] Comparative Preparation Example 2

[0210] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 100 parts by weight of 2,4-diphenyl-4-methyl-1-pentene is added and phenylvinylsilane is not added to obtain comparative self-polymer 2.

[0211] Comparative Preparation Example 3

[0212] This comparative preparation example provides a method for preparing a copolymer, which is different from comparative preparation example 1 in that diphenyldivinylsilane is used instead of phenyltrivinylsilane to obtain comparative self-polymer 3.

[0213] Comparative Preparation Example 4

[0214] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 1 in that 75 parts by weight of phenyltrivinylsilane and 25 parts by weight of 2,4-diphenyl-4-methyl-1-pentene are added to obtain comparative copolymer 4.

[0215] Comparative Preparation Example 5

[0216] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that methyltrivinylsilane is used instead of phenyltrivinylsilane to obtain comparative copolymer 5.

[0217] Comparative Preparation Example 6

[0218] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that tetraphenyldivinylsiloxane is used instead of phenyltrivinylsilane to obtain comparative copolymer 6.

[0219] Comparative Preparation Example 7

[0220] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that vinyl triethoxysilane is used instead of phenyl trivinyl silane to obtain comparative copolymer 7.

[0221] Comparative Preparation Example 8

[0222] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that 1,4-naphthoquinone is used instead of 2,4-diphenyl-4-methyl-1-pentene to obtain comparative copolymer 8.

[0223] Comparative Preparation Example 9

[0224] This comparative preparation example provides a method for preparing a copolymer, which is different from Preparation Example 3 in that n-dodecyl mercaptan is used instead of 2,4-diphenyl-4-methyl-1-pentene to obtain comparative copolymer 9.

[0225] Figure 1 The infrared spectra of copolymer 3, phenyltrivinylsilane and 2,4-diphenyl-4-methyl-1-pentene, wherein a is the infrared spectrum of 2,4-diphenyl-4-methyl-1-pentene, b is the infrared spectrum of phenyltrivinylsilane, and c is the infrared spectrum of copolymer 3. 1590cm -1The infrared characteristic absorption peak of "C=C" double bond is at 1590cm-1. Compared with 2,4-diphenyl-4-methyl-1-pentene and phenyltrivinylsilane, copolymer 3 has a strong absorption peak at 1590cm-1. -1 The characteristic absorption peak at 1428cm -1 、1110cm -1 The infrared characteristic absorption peak of "phenyl-Si" is 1401cm -1 、1006cm -1 、950cm -1 The infrared characteristic absorption peak of "vinyl-Si" is shown in Figure 3. By comparing the infrared spectra of phenyltrivinylsilane and copolymer 3, it can be seen that there is no obvious difference in the intensity of the "phenyl-Si" characteristic absorption peaks of the two, but the characteristic absorption peak of "vinyl-Si" of copolymer 3 is significantly weaker than that of phenyltrivinylsilane, which also indicates that some vinyl groups in copolymer 3 have undergone addition reaction.

[0226] Figure 2 is the NMR hydrogen spectrum of copolymer 3, phenyltrivinylsilane and 2,4-diphenyl-4-methyl-1-pentene (the standard substance is TSM tetramethylsilane), wherein a is the NMR hydrogen spectrum of phenyltrivinylsilane, b is the NMR hydrogen spectrum of 2,4-diphenyl-4-methyl-1-pentene, and c is the NMR hydrogen spectrum of copolymer 3. Among them, 7.0-7.5ppm is the characteristic peak area of ​​benzene ring, 4.5-6.5ppm is the characteristic peak area of ​​"C=C" (phenyltrivinylsilane and copolymer 3 are 5.5-6.5ppm, 2,4-diphenyl-4-methyl-1-pentene is 4.5-5.5ppm), 1.0-1.5ppm is -CH 3 Characteristic peak area; It can be found that the characteristic peak of "C=C" at 5.5-6.5ppm of copolymer 3 is significantly weakened compared with phenyltrivinylsilane, and the characteristic peak of "C=C" at 4.5-5.5ppm of 2,4-diphenyl-4-methyl-1-pentene disappears after copolymerization. At the same time, the "-CH 3 " Characteristic peak, it can be seen that phenyltrivinylsilane and 2,4-diphenyl-4-methyl-1-pentene undergo copolymerization to generate phenyltrivinylsilane-2,4-diphenyl-4-methyl-1-pentene copolymer 3.

[0227] Figure 3 Table 2 is a gel permeation chromatogram of the crude reaction product of copolymer 3. It can be seen from the graph that the crude reaction product contains polymer molecules with weight average molecular weights of 32,071 and 3,686, proving that the weight average molecular weight of copolymer 3 of the present invention is significantly larger than that of its raw material monomer, so copolymer 3 does undergo copolymerization.

[0228] Table 2 Gel permeation chromatography of the crude reaction product

[0229] name Retention time (min) Mn(Dalton) Mw(Dalton) MP (Dalton) Polydispersity area(%) Peak 1 19.550 20,839 32,071 19,944 1.539022 24.75 Peak 2 22.125 2,234 3,686 5,563 1.650171 22.17 Peak 3 29.308 73 79 77 1.080875 53.09

[0230] Testing of copolymers / comparison with homopolymers

[0231] Non-volatile matter test method

[0232] Weigh 1 gram of the unpurified copolymer of the preparation example, the crude product of the comparative self-polymer of the comparative preparation example, or the unreacted monomer compound in a tray, which contains a theoretical value of a1 grams of solvent, and the theoretical weight of the non-solvent part is (1-a1) grams. Bake in an oven at 170°C for 1 hour, weigh it after cooling, and calculate the non-volatile content as [a2 / (1-a1)]×100%. The results are shown in Table 3.

[0233] Table 3 Non-volatile content test results of the copolymers of the preparation examples and the crude products of the self-polymers of the comparative preparation examples and the monomers

[0234]

[0235] It can be seen that compared with the raw materials phenylvinylsilane and 2,4-diphenyl-4-methyl-1-pentene and the self-polymers of these monomers, the non-volatile matter of the copolymer of the preparation example is significantly increased and the volatility is greatly reduced.

[0236] This is because phenylvinylsilane and 2,4-diphenyl-4-methyl-1-pentene are low-viscosity liquids at room temperature and have a low boiling point. When directly baked at a high temperature greater than 150°C, they are easily volatilized. At the same time, when phenylvinylsilane or 2,4-diphenyl-4-methyl-1-pentene is self-polymerized, the monomer conversion rate is low, the self-polymerization reaction is difficult to control, and a copolymer with uniform molecular weight cannot be obtained, so its non-volatile content is also low. However, through the copolymerization of phenylvinylsilane and 2,4-diphenyl-4-methyl-1-pentene, a copolymer with a suitable molecular weight and not easy to volatilize at high temperature can be obtained.

[0237] Preparation of resin compositions and products thereof

[0238] The preparation method of the resin composition of the present invention comprises the following specific steps:

[0239] Preparation of varnish

[0240] The components of each embodiment (represented by E, such as E1 to E21) or comparative example (represented by C, such as C1 to C18) are added into a stirring tank according to the dosage in Tables 4 to 8, and stirred. The resin composition formed after uniform mixing is called resin varnish.

[0241] Taking Example E1 as an example, 100 parts by weight of copolymer 1 is added to a stirrer containing an appropriate amount of toluene and an appropriate amount of butanone, and stirred until the copolymer 1 is completely dissolved. Then, 50 parts by weight of KPU-6270 is added and stirred evenly. Then, 150 parts by weight of spherical silica SC-2050SMJ is added and stirred until completely dispersed. Then, 0.5 parts by weight of a curing accelerator (25B, first dissolved into a solution using an appropriate amount of solvent) is added and stirred for 1 hour to obtain a varnish of the resin composition E1.

[0242] In Tables 4 to 8, the addition amount of butanone and toluene is "appropriate amount", which means the amount of solvent used when the solvent addition amount makes the overall solid content of the resin composition reach the ideal solid content. For a resin composition using both butanone and toluene, "appropriate amount" means the total amount of the two solvents makes the overall solid content of the resin composition reach the ideal solid content, for example but not limited to 70 weight %.

[0243] Table 4 Composition of the resin composition of the embodiment (parts by weight)

[0244]

[0245]

[0246] Table 5 Composition of the resin composition of the embodiment (parts by weight)

[0247]

[0248] Table 6 Composition of the resin composition of the embodiment (parts by weight)

[0249]

[0250]

[0251] Table 7 Composition of comparative resin composition (parts by weight)

[0252]

[0253] Table 8 Composition of comparative resin composition (parts by weight)

[0254]

[0255]

[0256] Preparation of products

[0257] 1. Prepreg 1

[0258] The varnishes E1 to E21 prepared in the examples and the varnishes C1 to C18 prepared in the comparative examples were placed in an impregnation tank, and a glass fiber cloth (e.g., L-glass fiber cloth with a specification of 2116) was passed through the impregnation tank to allow the resin composition to adhere to the glass fiber cloth, and then heated at 120° C. to 170° C. to a semi-cured state (B-Stage), thereby obtaining a semi-cured sheet 1 (resin content of about 50%).

[0259] 2. Prepreg 2

[0260] The varnishes E1 to E21 prepared in the examples and the varnishes C1 to C18 prepared in the comparative examples were placed in an impregnation tank, and a glass fiber cloth (e.g., L-glass fiber cloth with a specification of 1078) was passed through the impregnation tank to allow the resin composition to adhere to the glass fiber cloth, and then heated at 120° C. to 170° C. to a semi-cured state (B-Stage), thereby obtaining a semi-cured sheet 2 (resin content of about 70%).

[0261] 3. Copper foil substrate 1

[0262] Two ultra-low profile copper foils (HVLP3 copper foils) with a thickness of 18 microns (Hoz) and eight prepregs 1 made from the resin compositions of the embodiments and comparative examples (2116L-glass fiber cloth is used, and the resin content of each prepreg is about 50%) are prepared respectively. They are stacked in the order of "one of the aforementioned copper foils / eight prepregs 1 / one of the aforementioned copper foils", and pressed for 130 minutes at 200°C under vacuum conditions to form each copper foil substrate 1. Among them, the eight stacked prepregs 1 will be cured (C-stage) to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 50%.

[0263] 4. Copper foil substrate 2

[0264] Two ultra-low profile copper foils (HVLP3 copper foils) with a thickness of 18 microns (Hoz) and two prepregs 1 made from the resin compositions of the embodiments and comparative examples (using 2116L-glass fiber cloth, the resin content of each prepreg is about 50%) are prepared respectively. They are stacked in the order of "one of the aforementioned copper foil / two prepregs 1 / one of the aforementioned copper foil", and pressed for 130 minutes at 200°C under vacuum conditions to form each copper foil substrate 2. Among them, the two superimposed prepregs 1 will be cured (C-stage) to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 50%.

[0265] 5. Copper foil substrate 3

[0266] Two ultra-low profile copper foils (HVLP3 copper foils) with a thickness of 18 microns (Hoz) and two prepregs 2 made from the resin compositions of the embodiments and comparative examples (1078L-glass fiber cloth is used, and the resin content of each prepreg is about 70%) are prepared respectively. They are stacked in the order of "one of the aforementioned copper foil / two prepregs 2 / one of the aforementioned copper foil", and pressed for 130 minutes at 200°C under vacuum conditions to form each copper foil substrate 3. Among them, the two superimposed prepregs 2 will be cured (C-stage) to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 70%.

[0267] 6. No copper substrate 1

[0268] The copper foil substrate 1 (composed of eight prepregs 1 laminated together) is etched to remove the copper foil on both sides to obtain a copper-free substrate 1 , which is composed of eight prepregs 1 laminated together and has a resin content of about 50%.

[0269] 7. No copper substrate 2

[0270] The copper foil substrate 2 (formed by laminating two prepregs 1) is etched to remove the copper foil on both sides to obtain a copper-free substrate 2 formed by laminating two prepregs 1 and having a resin content of about 50%.

[0271] 8. No copper substrate 3

[0272] The copper foil substrate 3 (formed by laminating two prepreg sheets 2) is etched to remove the copper foil on both sides to obtain a copper-free substrate 3 formed by laminating two prepreg sheets 2 and having a resin content of about 70%.

[0273] Product testing and characteristic analysis

[0274] 1. Glass transition temperature (Tg)

[0275] In the test of glass transition temperature, the copper-free substrate 1 is selected as the sample to be tested for dynamic mechanical analysis (DMA). The sample is heated at a heating rate of 2°C per minute, and the temperature is increased from 35°C to 300°C. The glass transition temperature (in °C) of each sample to be tested is measured according to the method described in IPC-TM-650 2.4.24.4.

[0276] The aforementioned copper-free substrate 1 was also selected as the sample to be tested for thermal mechanical analysis (TMA). The sample was heated at a heating rate of 10°C per minute, from 35°C to 300°C, and the glass transition temperature (in °C) of each sample to be tested was measured according to the method described in IPC-TM-6502.4.24.5.

[0277] As far as the art is concerned, the higher the glass transition temperature, the better. A glass transition temperature difference of 5°C or more indicates that there is a significant difference in the glass transition temperature between different substrates (there is a significant technical difficulty). For example, the glass transition temperature (DMA-Tg) of the article made of the resin composition disclosed in the present invention measured by the method described in IPC-TM-650 2.4.24.4 is greater than or equal to 220°C, for example, greater than or equal to 221°C, and for example, between 221°C and 260°C; the glass transition temperature (TMA-Tg) measured by the method described in IPC-TM-650 2.4.24.5 is greater than or equal to 200°C, for example, greater than or equal to 201°C, for example, between 201°C and 230°C.

[0278] 2. Copper foil tensile strength (also known as peel strength, peel strength, P / S)

[0279] The copper foil substrate 1 is cut into rectangular samples with a width of 24 mm and a length greater than 60 mm, and the surface copper foil is etched, leaving only a long strip of copper foil with a width of 3.18 mm and a length greater than 60 mm. The force (lb / in) required to pull the copper foil away from the substrate surface is measured using a universal tensile strength tester at room temperature (about 25°C) according to the method described in IPC-TM-650 2.4.8.

[0280] In the art, the higher the copper foil tensile strength, the better. The difference in copper foil tensile strength values ​​greater than or equal to 0.1 lb / in is a significant difference (there is a significant technical difficulty). For example, the copper foil tensile strength of the article made of the resin composition disclosed in the present invention is measured with reference to the method described in IPC-TM-650 2.4.8 and is greater than or equal to 2.00 lb / in, for example, between 2.00 lb / in and 3.00 lb / in.

[0281] 3. Ratio of thermal expansion

[0282] In the measurement of thermal expansion ratio (or dimensional change ratio), the aforementioned copper-free substrate 1 is selected as the sample to be tested for thermal mechanical analysis (TMA). The sample is heated at a heating rate of 10°C per minute, and the temperature is increased from 35°C to 265°C. The Z-axis dimensional change ratio of each sample to be tested (50°C-260°C temperature range, unit: %) is measured with reference to the method described in IPC-TM-650 2.4.24.5. The lower the dimensional change ratio percentage, the better.

[0283] Generally speaking, a high Z-axis thermal expansion coefficient of a substrate indicates a large dimensional change rate. For a copper foil substrate, a large dimensional change rate can easily lead to displacement of circuit contacts during the processing of the printed circuit board (such as but not limited to blind holes or buried holes), which reduces the yield, or causes problems such as board explosion that reduces reliability. In the art, the lower the percentage of thermal expansion, the better, and a significant difference is considered when the difference in thermal expansion is greater than or equal to 0.1%. For example, an article made of a resin composition disclosed in the present invention has a Z-axis thermal expansion coefficient measured by the method described in IPC-TM-650 2.4.24.5 that is less than or equal to 1.40%, for example, between 0.70% and 1.40%.

[0284] 4. X-axis thermal expansion coefficient (CTE)

[0285] In the measurement of the X-axis thermal expansion coefficient, the copper-free substrate 2 (made of two prepregs pressed together, with a resin content of about 50%) was selected as the sample to be tested for thermal mechanical analysis (TMA). The copper-free substrate was cut into samples with a length of 15 mm and a width of 2 mm, and the thickness of the sample was 8.4 mils. The sample was heated at a heating rate of 5°C per minute from 50°C to 260°C, and the X-axis thermal expansion coefficient (in ppm / °C) of each sample to be tested within the temperature range of 40°C to 125°C (α1) was measured according to the method described in IPC-TM-650 2.4.24.5.

[0286] Generally speaking, the lower the X-axis thermal expansion coefficient, the better the dimensional expansion and contraction characteristics. When the difference in the X-axis thermal expansion coefficient is greater than or equal to 0.1ppm / ℃, it is a significant difference (with significant technical difficulty). For example, the X-axis thermal expansion coefficient of each sample to be tested is low when the product made of the resin composition disclosed in the present invention is measured by referring to the method described in IPC-TM-650 2.4.24.5, for example, the X-axis thermal expansion coefficient is less than or equal to 11.0ppm / ℃, for example, between 7.5ppm / ℃ and 11.0ppm / ℃.

[0287] 5. Heat resistance after moisture absorption (PCT heat resistance)

[0288] The aforementioned copper-free substrate 1 sample was selected and subjected to a pressure cooking test (PCT) for 5 hours of moisture absorption (test temperature 121°C and relative humidity 100%) according to the method described in IPC-TM-650 2.6.16.1. Then, it was immersed in a tin furnace at a constant temperature of 288°C according to the method described in IPC-TM-650 2.4.23, and taken out after immersion for 20 seconds to observe whether the board exploded. For example, interlayer peeling between the insulating layers is considered to be a board exploded. Interlayer peeling will cause bubbling and separation between any layers of the substrate (visible to personnel).

[0289] For example, the product made of the resin composition disclosed in the present invention does not explode when subjected to a heat resistance test after moisture absorption for 5 hours in accordance with the method described in IPC-TM-650 2.6.16.1 and IPC-TM-650 2.4.23. The result of no explosion is recorded as "pass" to represent passing, and explosion is recorded as "fail" to represent failure.

[0290] 6. Dielectric constant (Dk) and dielectric loss factor (Df)

[0291] The aforementioned copper-free substrate 3 was selected as the sample to be tested. A microwave dielectrometer (purchased from AET Co., Ltd., Japan) was used to measure each sample to be tested at a frequency of 10 GHz according to the method described in JIS C2565.

[0292] In this field, the lower the dielectric constant or the lower the dielectric loss, the better the dielectric properties of the sample to be tested. When Dk is measured at a frequency of 10 GHz, and the Dk value is less than or equal to 3.50 and the Df value is less than or equal to 0.004, the difference in Dk value is greater than or equal to 0.05, which means that there is a significant difference between the dielectric constants of different substrates (there is a significant technical difficulty), and the difference in Dk value is less than 0.05, which means that there is no significant difference in the dielectric constant of the substrate; the difference in Df value is less than 0.00005, which means that there is no significant difference in the dielectric loss of the substrate, and the difference in Df value is greater than or equal to 0.00005, which means that there is a significant difference between the dielectric loss of different substrates (there is a significant technical difficulty). For example, the article made of the resin composition disclosed in the present invention has a dielectric constant less than or equal to 3.40, such as between 3.20 and 3.40, measured at a frequency of 10 GHz according to the method described in JIS C2565; and a dielectric loss less than or equal to 0.00300, such as between 0.00240 and 0.00300.

[0293] According to the above method, the characteristic test results of the embodiment and the comparative example are shown in Tables 9 to 13 below:

[0294] Table 9 Test results of properties of the resin composition of the embodiment

[0295] Characteristic test unit E1 E2 E3 E4 E5 E6 E7 DMA-Tg ℃ 249 238 253 242 247 243 239 TMA-Tg ℃ 220 212 223 211 215 213 210 P / S lb / in 2.0 2.0 2.2 2.4 2.4 2.4 2.4 Z-axis thermal expansion % 0.80 0.95 0.75 1.00 1.40 1.20 1.15 X-CTE ppm / ℃ 9.7 10.2 9.5 9.0 11.0 9.0 9.5 PCT(5hr) none pass pass pass pass pass pass pass Dk none 3.40 3.40 3.38 3.38 3.35 3.36 3.39 Df none 0.00290 0.00288 0.00285 0.00262 0.00260 0.00261 0.00263

[0296] Table 10 Characteristic test results of the resin composition of the embodiment

[0297] Characteristic test unit E8 E9 E10 E11 E12 E13 E14 DMA-Tg ℃ 234 225 221 235 248 230 260 TMA-Tg ℃ 210 204 201 210 215 210 230 P / S lb / in 2.5 2.6 2.7 2.4 2.6 2.6 2.4 Z-axis thermal expansion % 1.40 1.10 1.10 1.05 1.05 1.05 0.70 X-CTE ppm / ℃ 11.0 9.2 9.5 9.0 9.0 9.5 7.5 PCT(5hr) none pass pass pass pass pass pass pass Dk none 3.40 3.38 3.38 3.38 3.38 3.20 3.40 Df none 0.00264 0.00258 0.00254 0.00264 0.00280 0.00240 0.00300

[0298] Table 11 Characteristic test results of the resin composition of the embodiment

[0299] Characteristic test unit E15 E16 E17 E18 E19 E20 E21 DMA-Tg ℃ 245 237 250 238 237 236 240 TMA-Tg ℃ 215 210 220 210 213 210 224 P / S lb / in 2.4 2.6 2.4 2.5 2.4 2.4 3.0 Z-axis thermal expansion % 0.85 1.08 0.80 0.85 1.00 1.00 0.98 X-CTE ppm / ℃ 8.3 9.2 8.2 8.3 9.2 9.0 9.0 PCT(5hr) none pass pass pass pass pass pass pass Dk none 3.40 3.28 3.35 3.40 3.40 3.33 3.40 Df none 0.00290 0.00240 0.00270 0.00275 0.00257 0.00280 0.00288

[0300] Table 12 Characteristic test results of comparative resin composition

[0301]

[0302] Table 13 Characteristic test results of comparative resin composition

[0303]

[0304] According to the test results in Tables 9 to 13, the following phenomena can be observed.

[0305] The copolymer of phenyl vinyl silane and alkenyl compound retains a part of double bonds and has strong cross-linking reactivity. It can further participate in the cross-linking reaction when added to the resin composition, and can simultaneously improve the glass transition temperature, thermal expansion coefficient and dielectric loss characteristics of the product.

[0306] E1 to E3 prepared through the examples can confirm that the products prepared by the present invention, by using copolymers of phenyl vinyl silane and alkenyl compounds with styrene-terminated phenolic resins with different R-group structures, can achieve multiple or all of the functions of high glass transition temperature, high copper foil tensile force, low Z-axis thermal expansion rate, low X-axis thermal expansion coefficient, excellent PCT heat resistance, low dielectric constant and low dielectric loss characteristics.

[0307] By comparing E4 to E10 prepared in the examples with C1 to C4 prepared in the comparative examples, it can be confirmed that the copolymer of 80 to 98 parts by weight of phenyl vinyl silane and 2 to 20 parts by weight of alkenyl compounds used in the present invention can simultaneously achieve one, multiple or all of the technical effects of increasing the glass transition temperature, increasing the copper foil tensile force, reducing the Z-axis thermal expansion rate, reducing the X-axis thermal expansion coefficient, passing the PCT test and reducing the dielectric loss characteristics, compared with the copolymer or the self-polymer with the dosage outside the above range.

[0308] By comparing E4, E9-E12 prepared in the examples with C5-C9 prepared in the comparative examples, it can be confirmed that the copolymer of phenyl vinyl silane and alkenyl compound used in the present invention can simultaneously achieve one, multiple or all of the technical effects of increasing the glass transition temperature, increasing the tensile strength of copper foil, reducing the Z-axis thermal expansion rate, reducing the X-axis thermal expansion coefficient, reducing the dielectric constant and reducing the dielectric loss characteristics compared to the compounds whose monomer types are outside the above range.

[0309] By comparing E1, E4, E13-E16 prepared in the examples with C10-C12 prepared in the comparative examples, it can be confirmed that the present invention uses 100 parts by weight of a copolymer of phenyl vinyl silane and an olefinic compound in combination with 20-100 parts by weight of a styrene-terminated phenolic resin or further uses 5-30 parts by weight of a polyolefin resin. Compared with when the amount of styrene-terminated phenolic resin or polyolefin is outside the above range, the product prepared by the present invention can simultaneously achieve one, multiple or all of the technical effects of increasing the glass transition temperature, reducing the Z-axis thermal expansion rate, reducing the X-axis thermal expansion coefficient, passing the PCT test, reducing the dielectric constant and reducing the dielectric loss characteristics.

[0310] By comparing E4 prepared in the example with C14-C15 and C17 prepared in the comparative example; E10 prepared in the example with C13 and C15-C16 prepared in the comparative example; E9 prepared in the example with C18 prepared in the comparative example, it can be confirmed that the product prepared in the present invention by using the copolymer of phenyl vinyl silane and alkenyl compound can simultaneously achieve one, multiple or all of the technical effects of increasing glass transition temperature, increasing copper foil tensile force, reducing Z-axis thermal expansion rate, reducing X-axis thermal expansion coefficient, passing PCT test and reducing dielectric loss characteristics, compared with adding phenyl vinyl silane alone, adding alkenyl compound alone or adding phenyl vinyl silane and alkenyl compound without copolymerization.

[0311] By comparing E1 to E21 prepared in the examples with C1 to C18 prepared in the comparative examples, it can be confirmed that the present invention can achieve the technical effects of a glass transition temperature (TMA-Tg) greater than or equal to 201°C, a Z-axis thermal expansion coefficient less than or equal to 1.40%, an X-axis thermal expansion coefficient less than or equal to 11.0 ppm / °C, and a dielectric loss less than or equal to 0.00300 for the substrate by combining 80 to 98 parts by weight of phenyl vinyl silane with 2 to 20 parts by weight of a copolymer of an olefinic compound and 20 to 100 parts by weight of a styrene-terminated phenolic resin or further combining them with 5 to 30 parts by weight of a polyolefin. On the contrary, the comparative examples C1 to C18 that do not use the technical solution of the present invention cannot achieve the aforementioned technical effects.

[0312] The above embodiments are essentially only for auxiliary explanation and are not intended to limit the embodiments of the subject matter of the application or the application or use of these embodiments. In the present invention, the term "exemplary" means "as an example, example or illustration". Any exemplary embodiment of the present invention is not necessarily interpreted as being preferred or more advantageous than other embodiments.

[0313] In addition, although at least one exemplary embodiment or comparative example has been proposed in the aforementioned embodiment, it should be understood that the present invention can still have a large number of changes. It should also be understood that the embodiments described herein are not intended to limit the scope, use or configuration of the requested application subject matter in any way. On the contrary, the aforementioned embodiment will provide a simple guide for those skilled in the art to implement one or more of the embodiments described. Furthermore, various changes can be made to the function and arrangement of the elements without departing from the scope defined by the claims, and the claims include known equivalents and all foreseeable equivalents when the present patent application is filed.

Claims

1. A resin composition, characterized in that The resin composition comprises, by weight: 100 parts of a copolymer of phenylvinylsilane and an alkenyl compound, and 20 to 100 parts of a styrene-terminated phenolic resin; The copolymer of phenylvinylsilane and alkenyl compound comprises a structural unit formed by phenylvinylsilane and an alkenyl compound; the raw materials of the copolymer comprise phenylvinylsilane and an alkenyl compound, and based on the total weight of phenylvinylsilane and the alkenyl compound as 100 parts by weight, the phenylvinylsilane is 80 parts by weight to 98 parts by weight, and the alkenyl compound is 2 parts by weight to 20 parts by weight; The phenylvinylsilane has a structure represented by formula (1) and / or formula (2), the alkenyl compound has a structure represented by formula (3), and the styrene-terminated phenolic resin has a structure represented by formula (4): wherein Ra, Rb, Rc, and Rd are each independently H or a monovalent organic group, m and n are each independently an integer from 0 to 5, and Re, Rf, Rg, and Rh are each independently H or a monovalent alkyl group having 1 to 4 carbon atoms; Furthermore, R is at least one of a methylene group, a biscyclopentadienyl group, and a substituted or unsubstituted arylene group, and n1 is an integer of 1 to 10.

2. The resin composition according to claim 1, characterized in that The copolymer of phenylvinylsilane and an alkenyl compound has a weight average molecular weight of 2,000 to 50,000.

3. The resin composition according to claim 1, characterized in that The preparation method of the copolymer of phenylvinylsilane and alkenyl compound comprises: 80 to 98 parts by weight of phenylvinylsilane and 2 to 20 parts by weight of an alkenyl compound are reacted at 80 to 150° C. for 2 to 10 hours.

4. The resin composition according to claim 3, characterized in that The method for preparing the copolymer further comprises adding an initiator, a catalyst or a combination thereof.

5. The resin composition according to claim 1, characterized in that The copolymer of phenylvinylsilane and alkenyl compound comprises structural unit A and structural unit B, wherein the structural unit A is at least one of the structures represented by formula (5), formula (6), formula (7), formula (8) and formula (9), and the number of the structures represented by formula (5), formula (6), formula (7), formula (8) and formula (9) in the copolymer is J1, J2, J3, K1 and K2 respectively; The structural unit B is a structure represented by formula (10), and the number of the structures represented by formula (10) in the copolymer is L1; Wherein, * represents the bonding position, J1, J2, J3, K1, K2 are each independently 0 or a positive integer, but not 0 at the same time, and L1 is a positive integer; and 10≤J1+J2+J3+L1≤268, or 8≤K1+K2+L1≤212, or 8≤J1+J2+J3+K1+K2+L1≤268.

6. The resin composition according to claim 1, characterized in that The chemical structure of the alkenyl compound is at least one of formula (11), formula (12), and formula (13):

7. The resin composition according to claim 1, characterized in that The resin composition further comprises 5 to 30 parts by weight of a polyolefin resin.

8. The resin composition according to claim 1, characterized in that The resin composition also includes at least one of vinyl-containing polyphenylene ether resin, maleimide resin, maleimide triazine resin, small molecule vinyl-containing resin, prepolymer of small molecule vinyl-containing resin, styrene maleic anhydride resin, epoxy resin, phenol resin, benzoxazine resin, cyanate resin, polyester resin, polyamide resin, and polyimide resin.

9. The resin composition according to claim 1, characterized in that The resin composition further comprises at least one of an amine curing agent, a flame retardant, an inorganic filler, a curing accelerator, an inhibitor, a dye, a solvent, a toughening agent, and a silane coupling agent.

10. A product, characterized in that The product is made of the resin composition according to any one of claims 1 to 9, and the product includes but is not limited to a prepreg, a resin film, a laminate, a printed circuit board or a cured insulator.

11. The product according to claim 10, characterized in that The glass transition temperature of the product measured according to IPC-TM-650 2.4.24.4 method is greater than or equal to 220°C.

12. The article according to claim 10, characterized in that The glass transition temperature of the product measured with reference to the method described in IPC-TM-650 2.4.24.5 is greater than or equal to 200°C.

13. The article according to claim 10, characterized in that The copper foil tensile force of the product measured according to IPC-TM-650 2.4.8 method is greater than or equal to 2.00 lb / in.

14. The article according to claim 10, characterized in that The Z-axis thermal expansion coefficient of the product measured according to IPC-TM-650 2.4.24.5 method is less than or equal to 1.40%.

15. The article according to claim 10, characterized in that The X-axis thermal expansion coefficient of the product measured according to IPC-TM-650 2.4.24.5 method is less than or equal to 11.0 ppm / °C.

16. The article according to claim 10, characterized in that The dielectric constant of the product measured at a frequency of 10 GHz with reference to JIS C2565 method is less than or equal to 3.

40.

17. The article according to claim 10, characterized in that The dielectric loss of the product measured at a frequency of 10 GHz with reference to JIS C2565 method is less than or equal to 0.00300.

Citation Information

Patent Citations

  • Polyphenylene oxide resin, method of preparing polyphenylene oxide resin, polyphenylene oxide prepolymer and resin composition

    US20160185904A1

  • Styryl siloxy phenolic resin, and preparation method and application thereof

    CN108148162A

  • Resin composition and article made therefrom

    CN112646463A

  • Resin composition and product thereof

    CN112898773A

  • Phenol resin composition

    JP1999343387A